Evaluasi kadar CRP High Sensitivity sebagai Marker Risiko Kardiovaskular pada Dewasa Muda: Indonesia - Aldiano Rachmantiawan; Putu Ristyaning Ayu Sangging (CV. Jasa Sukses Abadi, 2026)
Atherosclerosis and cardiovascular disease originate from chronic low grade inflammatory processes, making high sensitivity C reactive protein or hs CRP widely studied as a cardiovascular risk marker, including in young adults. This study is a narrative review of 16 articles published between 2019 and 2025 that examine hs CRP in young adults aged 18 to 45 years and its association with cardiometabolic risk factors, cardiovascular disease events, and clinical outcomes. The review findings indicate that in overweight or obese young adults, elevated hs CRP levels are associated with central obesity, atherogenic dyslipidemia, impaired fasting glucose, and higher blood pressure. In addition, irregular sleep patterns and short term variability in diastolic blood pressure are also linked to increased hs CRP levels, suggesting the presence of subclinical inflammation early in life. In older populations and in patients with established cardiovascular disease, high hs CRP levels are reported to predict cardiovascular disease incidence, carotid plaque formation, cardiometabolic multimorbidity, functional disability, and short term mortality. However, hs CRP is not associated with the progression of coronary artery calcification and demonstrates substantial intra individual variability. Overall, hs CRP has potential value as an additional marker to identify young adults at higher cardiovascular risk. Nevertheless, hs CRP is not sufficient as a single screening tool and should be interpreted alongside traditional cardiovascular risk factors and lifestyle patterns. Repeated measurements are recommended to improve risk assessment accuracy and to account for biological variability in hs CRP levels.